PENGARUH PROGRAM PELATIHAN DAN PENDIDIKAN, KINERJA INDIVIDU DAN PENGALAMAN KERJA PERSONAL TERHADAP EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA KOPERASI SIMPAN PINJAM DI KECAMATAN MARGA TABANAN - Elinda Novita Sari; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2020)
Effective application of information systems can be influenced by training and education programs, individual performance, and personal work experience. The population used in this study were all Savings and Credit Cooperatives employees in Marga District, Tabanan as many as 145 employees. The method of determining the sample using purposive sampling technique so that the sample obtained 65 people as respondents. After testing the instruments and testing the classical assumptions, data analysis is then performed using multiple linear regression analysis, determination, t test, and F test. The results of the analysis show that the effect of training and education programs on the effectiveness of the use of accounting information systems obtained a regression coefficient of 0.147, t count value of 2.685 and t test significance value of 0.009 <0.05, so H1 is accepted. The effect of individual performance on the effectiveness of the use of accounting information systems obtained a regression coefficient of 0.637, a value of t arithmetic of 5.585 and a significant value of t test of 0.000 <0.05, so that H2 is accepted. The influence of personal work experience on the effectiveness of the use of accounting information systems obtained a regression coefficient of 0.213, a calculated t value of 2.040 and a significant value of the t test of 0.046 <0.05, so that H3 is accepted.